(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
Ippolito Cafici (1857-1947) played an important role in the italian palethnological scene between the nineteenth and twentieth century. In this paper the relationships with Gaetano Chierici Luigi Pigorini and Pellegrino Strobel, the three co-founders of “Bullettino di Paletnologia Italiana”, are analyzed through a number of unpublished archival documents. The collected material allows us to reconstruct an interesting overview into the dynamics within the "Bulletino" and to show the leading role played by Luigi Pigorini in the scientific formation of the young Cafici. Ultimately it shows the figure of a prominent scholar in the scientific debate of the epoch, and at the same time aware of the fundamental role of culture in the formation of national identity.